OPTIMALISASI PENGGUNAAN LAHAN UNTUKAGROFORESTRI DI DAERAH ALIRAN SUNGAI CIMANUK PROPINSI JAWA BARAT - Caya, Totok Gunawan, Suratman Woro Suprodjo, dan Lutfi Muta’ali (Jurnal Teknosains, 2014)
Watershed-based management in areas at the boundary of water sheds until now has not been realized. Basicadministrative process is still practiced in management, and sectoral ego is still high. Though watershed area is asystem, when an error occurs in the upper management, it will have an impact on down stream are as. Watershedmanagement is still focused on the economic benefits compared to environmental aspects. This research aims todevelop land evaluation models and economic evaluation to support the optimization of the use of land-based agroforestry. This study uses the physicall and evaluation with Ver.1.0 SPKL land evaluation model, which aims todetermine the level of suitability of the land for agro forestry crops and the economic valuation of environmentalservices approach. The results of this study are in the form of land use optimization appropriate tothe physicaland economic aspects of the approach, for the development of sustainable agriculture(agro forestry). The resultsobtained from this research can bring an idea about the amount(dollars) that can be produced by a plant agroforestry.